Return to Learn ECHO: Telementoring for School Personnel to Help Children Return to School and Learning After Mild Traumatic Brain Injury - McAvoy, Karen; Halstead, Mark; Radecki, Linda; Shah, Amy; Emanuel, Anjie; Domain, Stephanie; Daugherty, Jill; Waltzman, Dana (The Journal of school health, 2022)
ABSTRACT BACKGROUND Return to learn (RTL) after mild traumatic brain injury (mTBI) presents unique challenges for school professionals. A multidisciplinary team approach is necessary yet training school professionals is logistically difficult. This paper describes an innovative pilot RTL program and its evaluation. METHODS Utilizing the telehealth/telementoring program Project ECHO® (Extension for Community Healthcare Outcomes), this study utilized a multidisciplinary team of subject matter experts to deliver five 1‐hour sessions across 5 cohorts of school‐based professionals (total of 133 participants). The evaluation used a mixed‐methods approach of post‐session and post‐program participant surveys and post‐program participant focus groups. RESULTS Participants who completed a post‐program survey reported statistically significant improvements in essential aspects of RTL knowledge and self‐efficacy. This included improvements in how to manage a student with an mTBI (44.8% to 86.9%), benefits of early return to school for students following mTBI (31.8% to 86.9%), and the importance of written RTL policies/procedures (55.1% to 97.1%). CONCLUSIONS This study demonstrates that RTL training via a telementoring approach may be a positive and effective way to train school‐based professionals and improve knowledge and self‐efficacy, especially when attending face‐to‐face trainings are difficult. This model has the potential to produce programmatic and systematic improvements for RTL education.